2022
DOI: 10.3389/fimmu.2022.978513
|View full text |Cite
|
Sign up to set email alerts
|

Applications of nanobodies in brain diseases

Abstract: Nanobodies are antibody fragments derived from camelids, naturally endowed with properties like low molecular weight, high affinity and low immunogenicity, which contribute to their effective use as research tools, but also as diagnostic and therapeutic agents in a wide range of diseases, including brain diseases. Also, with the success of Caplacizumab, the first approved nanobody drug which was established as a first-in-class medication to treat acquired thrombotic thrombocytopenic purpura, nanobody-based the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 153 publications
0
11
0
Order By: Relevance
“…Again, nanobodies could come to the rescue thanks to their smaller size and different physicochemical properties [57]. The group of Pierre Lafaye demonstrated that nanobodies are superior to conventional antibodies when it comes to diffusion into fixed brain tissues [58], or as BBB‐permeable probes in vivo that are able to detect both intracellular and extracellular brain targets [59].…”
Section: Nanobodies Are Superior To Target Brain Tumorsmentioning
confidence: 99%
“…Again, nanobodies could come to the rescue thanks to their smaller size and different physicochemical properties [57]. The group of Pierre Lafaye demonstrated that nanobodies are superior to conventional antibodies when it comes to diffusion into fixed brain tissues [58], or as BBB‐permeable probes in vivo that are able to detect both intracellular and extracellular brain targets [59].…”
Section: Nanobodies Are Superior To Target Brain Tumorsmentioning
confidence: 99%
“…We used a previously characterized, fluorescently conjugated nanobody directed against human tau (pS422) (VHH-A2-488), which stains Alzheimer's and P301L tauopathy mouse brain (24) comparably to AT8 (16), and an antip-tau monoclonal antibody widely used to monitor pathology (25)(26)(27)(28). Because of their smaller size and other inherent features (29,30), we expected VHH-A2-488 to better penetrate and diffuse through large tissue volumes-essential for serial two-photon tomography (STPT). We optimized a protocol for permeabilization, immunolabeling and washing compatible with whole brain staining of p-tau (Fig.…”
Section: Development Of Whole Brain P-tau Staining and Quantification...mentioning
confidence: 99%
“…Following washes, ow cytometry was employed for subsequent analysis. 19. Model To facilitate subsequent molecular dynamics simulations, we diligently crafted three pivotal molecular structures: Nb 457 -Fc, Nb 457 -Nb HSA -Nb 457 , and the HIV-1 CH058 gp120.…”
Section: Assessment Of Nb457's In Uence On Cd4 Binding To Cell Surfac...mentioning
confidence: 99%
“…Importantly, our data, as well as other reports, indicated that nanobodies offered a unique binding mode to target proteins when compared to traditional antibodies, leading to remarkably potent neutralization against viral infections [15][16][17] . Following the approval of Caplacizumab, the rst camelderived nanobody, for marketing in 2018 18 , numerous nanobodies currently have been in clinical trials including ALX-0651 for tumors, ALX-0171 for RSV virus, and ALX for in ammation 12,13,19 , underscoring the signi cant therapeutic potential of nanobodies. Thus far, anti-CD4 nanobodies have been developed and utilized for in vivo CD4 cell tracing 20 , while no anti-CD4 nanobodies have yet been developed for the therapeutic purpose of neutralizing HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%